2018
DOI: 10.5902/2179460x31681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intestinal histological damage in zebrafish exposed to environmentally relevant concentrations of manganese

Abstract: Manganese is an essential element for many physiological processes. However, in prolonged exposures or at high concentrations it may present toxicity to several organs, which has made it an object of study in pharmacological, behavioral, neurological and environmental research in different organisms. Thus, it was aimed to evaluate the damage caused by acute and chronic exposures to this element, through the histopathological analysis of the zebrafish (Danio rerio) intestine. Samples were embedded in paraffin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…According to Authman et al (2015), heavy metals such as mercury, cadmium, copper, lead and zinc are of the most important pollutants which affect aquatic environment and fish. Rodrigues et al (2018) did not observe significant histopathological changes in the intestine of the species Danio rerio in the acute experiment, however, there was a tendency for increased histological changes as MnCl2 concentrations increased. Lamas et al (2007) reported several specific advantages in describing the natural characteristics of aquatic systems and in assessing changes to habitats.…”
Section: Epithelialcontrasting
confidence: 60%
“…According to Authman et al (2015), heavy metals such as mercury, cadmium, copper, lead and zinc are of the most important pollutants which affect aquatic environment and fish. Rodrigues et al (2018) did not observe significant histopathological changes in the intestine of the species Danio rerio in the acute experiment, however, there was a tendency for increased histological changes as MnCl2 concentrations increased. Lamas et al (2007) reported several specific advantages in describing the natural characteristics of aquatic systems and in assessing changes to habitats.…”
Section: Epithelialcontrasting
confidence: 60%
“…Lastly, MnCl 2 used to create elevated water Mn might have impacts on fish physiology. Studies have revealed changes in intestinal epithelium (Rodrigues et al ., 2018) and a 10 times higher activity of peroxidase, which is usually used due to the toxicity‐generated reactive oxygen species, in fish brain (Altaf et al ., 2016). Nonetheless, both studies involved high treatments of Mn of approximately 7 mg l −1 or 70 mg l −1 compared to 0.55 mg l −1 in this study, suggesting the impacts of MnCl 2 in this study might be weak.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the intestine analysis, 5 fields per animal were analyzed by evaluating the percentage of altered villi in each field (2 villi per field). The increase in the thickness of intestinal villi, leukocyte infiltration, and presence/absence of eosinophils were registered according to the classification used by Rodrigues et al (2018). The percentage of cellular alterations was calculated, and the number of intestinal goblet cells was also counted.…”
Section: Histological Proceduresmentioning
confidence: 99%